Sharia Compliance in Implementing Qardh Using Customer Funds: Analysis of DSN Fatwa No. 79/DSN-MUI/III/2011 with Comparison of AAOIFI Standards - Amalia Muazzah Adawiah; Rifdah Nabilatuzain; Insan Nadhif Ramadhan (Mabahits Al-Uqud, 2025)
This study examines Sharia compliance in the implementation of Qardh using customer funds in Islamic financial institutions, focusing on the provisions of Fatwa DSN No. 79/DSN-MUI/III/2011 and its comparison with the international AAOIFI standards. The research employed a literature review method with document analysis of regulations, fatwas, and official reports of financial institutions. Source selection covered publications and regulations from 2011 to 2024, accessed through national and international databases, with thematic relevance and source authority as the main criteria. The findings reveal that the implementation of Qardh, as practiced by Bank Syariah Indonesia through a gold-collateralized Qardh scheme, formally complies with the fatwa and AAOIFI standards. However, several compliance risks were identified, including indirect benefits from the use of collateral, potential hidden riba in non-transparent administrative fees, and limited access due to rigid Financing-to-Value (FTV) policies. This study recommends concrete measures such as blockchain-based fund tracking, digital Sharia audits, standardized administrative fees, flexible FTV for vulnerable customers, and open public reporting. These findings are expected to strengthen Qardh’s role as a fair, transparent, and socially oriented Islamic financial instrument.